(untitled) (Bioscience Journal, 2023)
Although lettuce is one of the most important vegetable crops cultivated in Brazil, producers conduct seedling production empirically, as there are no published reports on the optimal start time and management strategy for seedling fertigation. The present aimed to assess the influence of fertigation management on the growth, physiological aspects and nutritional status of lettuce seedlings and to determine the optimal fertigation start time and frequency. Two experiments were conducted, each with a randomized block design and six repetitions. The first consisted of six treatments, namely six fertigation start times at 0, 3, 6, 9, 12, and 15 d after emergence (DAE), and the second consisted of five treatments, representing different application frequencies at 3, 4, 5, 6, and 7 d intervals. The assessment of nutrient accumulation levels and biometric and physiological characteristics of the seedlings were performed after transplanting. Fertigation start times significantly affected 14 of the 18 variables assessed, particularly the number of leaves, shoot dry weight, leaf area, initial chlorophyll fluorescence, and P, K, Ca, Mg, and S accumulation. The best results for ten variables were obtained when fertigation began at emergence, with values 17.77 - 35.63% higher than those at fertigation onset at 15 DAE. Application frequency only influenced chlorophyll content and N, P, K, and S accumulation, with optimal results obtained at 3 - 6 d intervals. Beginning fertigation at plant emergence favors dry weight production, nutrition and photosynthesis and shortens the production time of lettuce seedlings. The optimal start time for lettuce seedling fertigation is at emergence, with application performed every 6 d.